2019
DOI: 10.1002/jcb.29568
|View full text |Cite
|
Sign up to set email alerts
|

Retracted: Circular RNA ACR relieves high glucose‐aroused RSC96 cell apoptosis and autophagy via declining microRNA‐145‐3p

Abstract: Retraction: ‘Circular RNA ACR relieves high glucose‐aroused RSC96 cell apoptosis and autophagy via declining microRNA‐145‐3p’, by Ying Liu, Xiaoqing Chen, Jingjing Yao, Jing Kang, J Cell Biochem. The above article, published online on 30 December 2019 in Wiley Online Library (https://onlinelibrary.wiley.com/doi/abs/10.1002/jcb.29568), has been retracted by agreement between the the journal's Editor in Chief, Prof. Dr. Christian Behl, and Wiley Periodicals LLC. The retraction has been agreed following an invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 52 publications
2
14
0
1
Order By: Relevance
“…The PI3K/AKT/mTOR pathway has also been revealed to be closely associated with autophagy ( 24 , 25 ). In addition, Liu et al ( 26 ) demonstrated that the PI3K/AKT signaling pathway was inhibited in a hyperglycemic environment, Autophagy-related circular RNA can attenuate autophagy and ROS production in Schwann cells subjected to hyperglycemia by promoting the activation of the PI3K/AKT/mTOR pathway ( 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…The PI3K/AKT/mTOR pathway has also been revealed to be closely associated with autophagy ( 24 , 25 ). In addition, Liu et al ( 26 ) demonstrated that the PI3K/AKT signaling pathway was inhibited in a hyperglycemic environment, Autophagy-related circular RNA can attenuate autophagy and ROS production in Schwann cells subjected to hyperglycemia by promoting the activation of the PI3K/AKT/mTOR pathway ( 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al discovered that the expression of circACR was reduced in HG-irritated rat Schwann RSC96 cells, which relieved the oxidative stress caused by HG via declining miR-145-3p and promoting PI3K/AKT/mTOR pathway activation [ 95 ].…”
Section: Regulatory Role Of Circrnas In Oxidative Stress: Implicatmentioning
confidence: 99%
“…High glucose (HG) induces the downregulation of circACR in RSC96 cells. CircACR may downregulate the expression of miR-145-3p and promote the activation of the PI3K/AKT/mTOR pathway to alleviate HG-induced apoptosis, autophagy, and ROS generation in RSC96 cells ( Liu et al, 2019 ). Heat stress may enhance the generation of oxidative stress ( Slimen et al, 2014 ).…”
Section: Research Progress On Circrnas and Oxidative-stress‒related Diseasesmentioning
confidence: 99%